2012
DOI: 10.1111/j.1463-1318.2011.02719.x
|View full text |Cite
|
Sign up to set email alerts
|

Transperineal omentum flap for the anatomic reconstruction of the rectovaginal space in the therapy of rectovaginal fistulas

Abstract: Complete omental reconstruction of the rectovaginal space appears decisive in the operative therapy of deep rectovaginal or enterovaginal fistulas. Comparative studies on standard therapies are necessary although direct comparison of case series is difficult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…79,80 However, inferior results are seen in irradiated patients. 81,82 Due to good results and low morbidity, proponents of mesh suggest that this technique should be the first step in the treatment of RVF, prior to GMFI. Larger randomized trials are needed to better evaluate the role and cost-effectiveness of bioabsorbable mesh in the management of complex RVF.…”
Section: Bioabsorbable Mesh Interpositionmentioning
confidence: 99%
See 1 more Smart Citation
“…79,80 However, inferior results are seen in irradiated patients. 81,82 Due to good results and low morbidity, proponents of mesh suggest that this technique should be the first step in the treatment of RVF, prior to GMFI. Larger randomized trials are needed to better evaluate the role and cost-effectiveness of bioabsorbable mesh in the management of complex RVF.…”
Section: Bioabsorbable Mesh Interpositionmentioning
confidence: 99%
“…If the rectum is relatively preserved, separation of the fistula with omental interposition offers success rates of 90 to 100%. 82,83 If the rectum is damaged and anal function is preserved, low anterior resection with fistula tract excision and coloanal anastomosis can be performed. 84…”
Section: Transabdominalmentioning
confidence: 99%
“…A mobilized, pedicled omental graft has been described in treatment of complex rectovaginal fistulas. 9 The omentum has a good blood supply, derived from the left and right gastroepiploic arteries; it is known for its role in resolving (abdominal) infections and has been successfully used in complicated vaginal fistula repair. In our study, the omental graft was used in one patient with a pouch-neovaginal fistula with a good result and without any complications.…”
Section: Discussionmentioning
confidence: 99%
“…Bricker-Johnston sigmoid colon graft [ 30 ] and its modification proposed by Steichen [ 31 ] was successfully applied in a 61-year-old female with RI-RVF with good functional results but following the three-stage procedure. More recently, Zimmermann described the ultra-deep anterior rectum resection with transperineal and transvaginal omentum reconstruction coupled with protective ileostomy construction that his team used to treat a 37-year-old woman with RI-RVF [ 32 ]. Authors of these reports observed that the described techniques are efficient in cases of high fistulas and emphasized the careful selection of patients fit for the procedures.…”
Section: Discussionmentioning
confidence: 99%